2009
DOI: 10.1007/s12565-008-0005-y
|View full text |Cite
|
Sign up to set email alerts
|

Morphological study of the communication between the musculocutaneous and median nerves

Abstract: We investigated the incidence of each pattern of the communications between the musculocutaneous and median nerves and discussed its morphological significance. The communications between both nerves were seen in 188 (41.5%) of 453 specimens. They were classified into five regular patterns according to their directions and formations. The incidence of the communication was significantly higher in those with excessive heads of biceps brachii than in those without them (p < 0.05). As a result, we established a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 2 publications
(3 reference statements)
7
34
2
4
Order By: Relevance
“…The AHBB associated with the simultaneous presence of the communicating branch between the musculocutaneous and median nerves observed in our series in 23.8% of the cases, is a characteristic also described in the works by Kosugi et al [9] and Maeda et al [12], who reported this trait in 27.8% and 30.1%, respectively, in Japanese populations. Having in mind the presence and location of the communicating branch in the mid or lower thirds of the arm associated to muscle variants, such as the AHBB during surgical approaches, will possibly decrease the risk of injuring these structures.…”
Section: Discussionsupporting
confidence: 89%
“…The AHBB associated with the simultaneous presence of the communicating branch between the musculocutaneous and median nerves observed in our series in 23.8% of the cases, is a characteristic also described in the works by Kosugi et al [9] and Maeda et al [12], who reported this trait in 27.8% and 30.1%, respectively, in Japanese populations. Having in mind the presence and location of the communicating branch in the mid or lower thirds of the arm associated to muscle variants, such as the AHBB during surgical approaches, will possibly decrease the risk of injuring these structures.…”
Section: Discussionsupporting
confidence: 89%
“…Communications between McN and MN were observed in 48% [9] or 57.3% [7] of those cases with the excessive head of the BBM. The combined neuromuscular variations were classified by Kosugi et al [7] as follows: Group I is a pattern without the communication between the McN and the MN (42.7%); Group II has a communicating branch from the McN to the MN (32%); Group III has a branch running from the MN to the McN (16%), Group IV has above 2 communications (6.7%), and Group V has various other patterns (2.7%).…”
Section: Discussionmentioning
confidence: 97%
“…In the absence of the MCN, its fibers are fused with the MN forming a common trunk. In this case, the branches for the muscles of the anterior compartment of the arm and the lateral antebrachial cutaneous nerve arises from the median nerve (Maeda et al, 2009;Bulla et al). This corresponds to Le Minor classification type V. Studies by Beheiry reported that in MCN absence the branch for the CbM may arise from the lateral cord of the brachial plexus and not from the median nerve.…”
Section: Discussionmentioning
confidence: 99%